Secondary forests of the Himalaya with emphasis on the north-eastern hill region of India - Ramakrishnan, P.S.; Kushwaha, S.P.S. (2001)
Secondary forests form a major component of the forest types in the Central Himalayan region and in the north eastern hills of India. Deforestation in these areas is largely due to external pressures of timber extraction for industrial use. When large scale deforestation from outside the region is superimposed upon the demands of the local communities for food, fodder and fuelwood, the previously balanced use of forest resources, including the management of swidden fallow secondary forests, becomes impaired. Understanding the local linkages between ecological and social processes is important in order to design strategies for the sustainable management of secondary forests in the region where traditional societies live. A particular approach suggested is to benefit from the sociocultural heritage related to keystone species such as Alnus nepalensis. The traditions around these and related species and their particular ecological attributes allow for the design of adaptive management strategies to resolve problems with both environmental and sociocultural dimensions. In designing such an adaptive management plan that could be operationalised at the landscape level where both natural and human managed agro ecosystems are well integrated, designing appropriate institutions at the local level is important for ensuring community participation.